2007
DOI: 10.1080/09513590701259542
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical hypothyroidism and thyroid autoimmunity in women with infertility

Abstract: We observed a higher prevalence of SH, but not of TAI, in patients with infertility. Our results support thyroid screening in women with reproductive failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
1
18

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(115 citation statements)
references
References 37 publications
7
89
1
18
Order By: Relevance
“…Abalovich et al have reported endometriosis was nearly 2 times more compared to control group (25% vs 14%) and Gerhard et al reported endometriosis was nearly 5 times more (44% vs 9%). 17,33 Similarly, in patients with polycystic ovarian disease ATA positivity was significantly higher compared to control group. 42,43 Even association of this antibody positivity with premature ovarian insufficiency was also suggested.…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 96%
See 1 more Smart Citation
“…Abalovich et al have reported endometriosis was nearly 2 times more compared to control group (25% vs 14%) and Gerhard et al reported endometriosis was nearly 5 times more (44% vs 9%). 17,33 Similarly, in patients with polycystic ovarian disease ATA positivity was significantly higher compared to control group. 42,43 Even association of this antibody positivity with premature ovarian insufficiency was also suggested.…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 96%
“…32 Incidence of SCH in normal population is estimated at 4-8.5%, but it was determined that in patients with infertility and in advanced age the incidence increases. 33 According to the current literature treatment of SCH is not established yet. In a prospective randomized study 64 SCH patients with infertility was delivered 50 mcg levothyroxine (LT4) in the first day of controlled ovarian stimulation (COH) and it was shown that having grade 1 and embryo, implantation and live birth rates were higher in the treatment group; but, no difference was found between groups regarding pregnancy rate per cycle.…”
Section: Subclinical Hypothyroidismmentioning
confidence: 99%
“…A high percentage of women with Chypo or SChypo become pregnant without being treated with T 4 (48). Abortion and stillbirth have been highly associated with TD, as well as endometriosis and ovarian failure, mostly in women with TAI (6).…”
Section: Obstetric Complications Associated With Td "mentioning
confidence: 99%
“…Effects of maternal hypothyroidism on offspring health are important in human [1] and veterinary medicine [2]. Previously, in the rat model, we have shown that maternal hypothyroidism during pregnancy and lactation leads to premature ovarian failure of pubertal and adult offspring [3].…”
Section: Introductionmentioning
confidence: 99%